MicroRNA expression correlates with disease recurrence and overall survival in oral squamous cell carcinoma. Issue 3 (March 2019) - Moratin, Julius; Hartmann, Stefan; Brands, Roman C.; Horn, Dominik; Fuchs, Andreas; Mutzbauer, Grit; Seher, Axel; Scholz, Claus; Müller-Richter, Urs D.A.; Linz, Christian
Abstract: Objectives: Locoregional disease recurrence and metastatic events are the leading causes of death and the most important prognostic factors in patients with head and neck squamous cell carcinoma (HNSCC). A major goal of oncology is the identification of clinical and molecular parameters to evaluate the individual risk of recurrence. MicroRNAs (miRNAs) have been shown to correlate well with tumor size and differentiation. Therefore, they are candidate biomarkers for estimating clinical outcomes. Materials and methods: In this study, the expression levels of distinct miRNAs extracted from formalin-fixed, paraffin-embedded (FFPE) samples of oral squamous cell carcinoma were compared. Results: Statistical analysis revealed significant correlations between distinct miRNAs and disease recurrence (miR-99*, miR-194*; p  < 0.05) and overall survival (miR-99*; p  < 0.05). The results were then validated via data from The Cancer Genome Atlas (TCGA). Conclusions: Our data show that miR-99* and miR-194* can possibly serve as biomarkers for clinical outcome in HNSCC. These findings may help to identify high-risk patients, who could profit from a more individualized treatment and follow-up.